Thermoelectric Materials: A Scientometric Analysis of Recent Advancements and Future Research Directions - Sami M. Ibn Shamsah (Energies, 2024)
This scientometric study looks at the current trend in thermoelectric materials research and explores the evolving domain of thermoelectric materials research using a combination of bibliometric and scientometric methodologies. The analysis examines global research trends from a dataset of over 37,739 research articles, focusing on thematic evolution, annual growth rates, and significant contributions. Six principal research clusters were identified, encompassing energy conversion, material synthesis and nanostructures (the most prominent cluster), computational modeling and material properties, measurement and characterization, material performance enhancement, and material processing and microstructure. Each cluster highlights a critical aspect of the field, reflecting its broad scope and depth. The key findings reveal a marked annual increase in research output, highlighting the growing global importance of thermoelectric materials in sustainable energy solutions. This is especially evident in the significant contributions from China and the USA, emphasizing their leadership in the field. The study also highlights the collaborative nature of thermoelectric research, showing the impact of global partnerships and the synergistic effects of international collaboration in advancing the field. Overall, this analysis provides a comprehensive overview of the thermoelectric materials research landscape over the past decade, offering insights into trends, geographic contributions, collaborative networks, and research growth. The findings underscore thermoelectric materials’ vital role in addressing global energy challenges, highlighting recent advancements and industrial applications for energy efficiency and sustainability.